Atrial arrhythmias arising from the Superior Vena Cava presenting as paroxysmal Atrial fibrillation and Atrial tachycardia - Dar, Javaid Ahmad; Naseem, Jahangir; Narasaiyan, Hariharan; Jagannath, Yogesh; Patloori, Sirish; Manickavasagam, Anand; Jacob, John; Chase, David (SA Heart Journal, 2024)
The Superior vena cava (SVC) harbours about 25%-40% of the non-pulmonary vein foci in Atrial Fibrillation (AF) and could manifest itself as paroxysmal Atrial Tachycardia (AT). AF ablation focusing on pulmonary vein isolation alone could miss SVC ectopy and result in failure of the procedure. Successful ablation is usually curative in SVC ectopy-induced AT/AF, however, potential complications include injury to the Phrenic nerve, Vagus nerve or the Sino-Atrial node. A focal ablation approach or SVC Isolation are both proven options in the management of SVC tachycardia. In this case series, we report SVC ectopy with variable conduction into the right atrium mimicking sinus rhythm, AT, Atrial Flutter (AFL) or AF.